Essential components of an educational program for implementing skin-to-skin contact for preterm infants in intensive care units: an integrative literature review - Takalani T. Denge; Nokwanda Edith Bam; Welma Lubbe; Annah Rakhudu (BMC, 2024)
Abstract Background Globally, prematurity is the primary factor behind the mortality of children under the age of 5 years, resulting in approximately 1 million children dying annually. The World Health Organization (WHO) recommends Skin-to-Skin Contact (SSC) as part of routine care for preterm infants. Evidence shows that SSC reduces mortality, possibly by improving thermoregulation, facilitating the earlier initiation of breastfeeding and reducing the risk of nosocomial infection. An educational program for implementing SSC has been demonstrated to enhance the knowledge and practice of parents and nurses in intensive care units. This study, the first of its kind in the North West Province (NWP), aims to identify the essential components of an educational program for implementing SSC for premature infants in intensive care units. Objective This paper presents an integrative literature review that critically synthesizes research-based literature on essential components of an educational program for implementing SSC for preterm infants in intensive care units. Methods A comprehensive search of electronic databases, such as CINAHL, MEDLINE, PsycINFO, ProQuest and Health Source: Nursing/Academic Edition and Health Source-Consumer Edition, was conducted using different keywords and references lists from the bibliography. Results Twelve articles relevant to this review were identified, read and synthesized to answer the research question. Three essential components emerged from the findings of this review, namely (1) the necessity of policy and role players for implementing SSC, (2) the availability of education and training, and (3) counseling and support for parents of preterm infants. Conclusions The outcomes of this study have the potential to facilitate the implementation and expansion of SSC in intensive care units. This could aid program implementers, policymakers, and researchers to implement and scale up this important tool in intensive care units.